Associations between physical activity and cardiorespiratory fitness with vascular health phenotypes in older adults: a cross-sectional study - de Sousa, Maria Karolina Ferreira; Silva, Raíssa de Melo; Freire, Yuri Alberto; Souto, Gabriel Costa; Câmara, Marcyo; Cabral, Ludmila Lucena Pereira; Macêdo, Geovani Araújo Dantas; Costa, Eduardo Caldas; Oliveira, Ricardo Santos (Frontiers in Physiology, 2023)
Objective: We investigated the associations between physical activity (PA) and cardiorespiratory fitness (CRF) with vascular health phenotypes in community-dwelling older adults. Methods: This cross-sectional study included 82 participants (66.8 ± 5.2 years; 81% females). Moderate-to-vigorous physical activity (MVPA) was assessed using accelerometers, and CRF was measured using the distance covered in the 6-min walk test (6MWT). The vascular health markers were as follows: i) arterial function measured as aortic pulse wave velocity (aPWV) estimated using an automatic blood pressure device; and ii) arterial structure measured as the common carotid intima-media thickness (cIMT). Using a combination of normal cIMT and aPWV values, four groups of vascular health phenotypes were created: normal aPWV and cIMT, abnormal aPWV only, abnormal cIMT only, and abnormal aPWV and cIMT. Multiple linear regression was used to estimate the beta coefficients (β) and their respective 95% confidence intervals (95% CI) adjusting for BMI, and medication for diabetes, lipid, and hypertension, sex, age, and blood pressure. Results: Participants with abnormal aPWV and normal cIMT (β = −53.76; 95% CI = −97.73—−9.78 m; p = 0.017), and participants with both abnormal aPWV and cIMT (β = −71.89; 95% CI = −125.46—−18.31 m; p = 0.009) covered less distance in the 6MWT, although adjusting for age, sex and blood pressure decreased the strength of the association with only groups of abnormal aPWV and cIMT covering a lower 6MWT distance compared to participants with both normal aPWV and cIMT (β = −55.68 95% CI = −111.95–0.59; p = 0.052). No associations were observed between MVPA and the vascular health phenotypes. Conslusion: In summary, poor CRF, but not MVPA, is associated with the unhealthiest vascular health phenotype (abnormal aPWV/cIMT) in older adults.